The Socio-Economic Movements of Sufis: Exploring Spiritual Entrepreneurship of the Idrisiyyah Ṭarīqah at Pagendingan Tasikmalaya Indonesia - Ismail, Asep Usman (ILMU USHULUDDIN, 2023)
Idrisiyyah's spiritual entrepreneurship was born from the neo-Sufism paradigm which produced a business ethos with the motivation of worship, professional service to the murshid, a symphony of inner and outer life and a modern and professional business management culture for the Islamic boarding school's economic independence. Apart from that, Idrisiyyah's entrepreneurial spirituality also gave birth to Idrisiyyah's distinctive corporate culture and corporate values which caused Idrisiyyah business people to feel inner satisfaction, priceless. Cannot be compensated with money, objects or any kind of materials. This causes Idrisiyyah's spiritual entrepreneurship to become an oasis in the midst of a business ethics crisis; but it is difficult to put into practice in society, because Idrisiyyah's spiritual entrepreneurship is tied to the Tarîqah system. The key to success lies in applying the concepts of lillah, fillah and billah, for Allah, in Allah's rules and by Allah, in all lines of business in the epicenter of murshid leadership and example.